Food enzymes immobilization: novel carriers, techniques and applications. (February 2022) - Xie, Jiayu; Zhang, Yi; Simpson, Benjamin
Highlights: Innovative carrier materials to immobilize food enzymes. Cost effective technologies to fabricate immobilized food enzymes. Productive and sustainable applications of immobilized food enzymes. Abstract : Food enzyme immobilization is a technology to mitigate various limitations of free enzymes in food processing. Versatile carriers such as agro-waste based materials, nano materials, and metal organic frameworks are developed to immobilize enzymes with improved enzymological characteristics to enable catalytic reactions to be carried out under sophisticated and extreme processing conditions. New fabrication technologies of immobilized food enzymes, for example, 3D printing and coaxial electrospraying also enhance enzyme functionality. Recent research on food enzyme immobilization is aimed at sustainability, cost-effectiveness, automation, high-throughput, multifunction, and safety. These developments enable new applications in food bioprocessing, food analyses, food control and food packaging, and so on.